Impact of Rupiah Exchange Rate Fluctuations on Export-Import Performance: A Systematic Literature Review - Agus Rohmat Hidayat (Journal of Sharia Micro Enterprise and Cooperation, 2026)
Background: Rupiah exchange rate fluctuations against the US dollar play a critical role in Indonesia's export-import performance and overall economic stability. Depreciation may enhance export competitiveness but increase import costs, while appreciation has the opposite effect. Understanding these dynamics is essential for policymakers, businesses, and investors. Objective: This study aims to analyze the impact of rupiah exchange rate volatility on Indonesia's export and import performance, assess its effects on corporate profitability and stock returns, and examine financial and monetary strategies to mitigate associated risks. Method: A systematic literature review (SLR) was conducted, analyzing 30 relevant studies from 2022–2026 covering monetary policy, credit risk, macroeconomic stability, and financial strategies for MSMEs. Both empirical and theoretical literature were synthesized to provide a comprehensive overview. Result: Findings indicate that rupiah depreciation increases export competitiveness but pressures import costs and domestic prices. Exchange rate volatility significantly affects company profitability, stock returns, and banking sector performance, especially BPRs supporting MSMEs. Mitigation strategies, including adaptive monetary policy, soft loans, and digital financial solutions like QRIS, effectively reduce risks and stabilize financial outcomes. Conclusion: A comprehensive understanding of rupiah exchange rate fluctuations is crucial for optimizing trade performance and ensuring economic stability. Policymakers and businesses should implement adaptive strategies and leverage financial innovations to mitigate risks, enhance export competitiveness, and support sustainable economic growth.